Danish Stød in Compounds: A Stratal Match Theory Analysis - Yonatan Goldshtein (Catalan Journal of Linguistics, 2025)
Stød is a laryngeal prosody residing on particular Danish syllables (Fischer-Jørgensen 1989). The distributional rules of stød are exceedingly complex, and especially the prosody of Danish compounds has played a central role in recent theoretical work on the phonology of compounds and prosodic recursion driven by the morphology-phonology interface (Ito & Mester 2015, 2021). Whereas previous work accounts for a subset of relatively simple, well-behaved compounds, the present article offers a comprehensive analysis of the phonology of stød in Danish compounds including two different types of lexical exceptions. For this analysis, the article proposes an implementation of Match Theory (Selkirk 2011; Ishihara & Kalivoda 2022) within the broader framework of Stratal Optimality Theory (Bermúdez-Otero 2018). This combined framework, Stratal Match Theory, provides a restrictive theory for the construction of prosodic structure at the morphology-phonology interface and offers a principled approach to lexical exceptions applicable beyond the phonology of Danish compounds.